Proceedings of the 1st International Conference on Community Health (ICCH 2019) 2020
DOI: 10.2991/ahsr.k.200204.037
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Body Mass Index and Risk of Obesity with Blood Pressure Women

Abstract: Obesity is one of the epidemic diseases in most developed countries. According to the WHO report states that more than 1.9 billion adults worldwide are overweight and more than 600 million people are obese, corresponding to 39% overweight and 13% obesity rates for the adult population in the world. Obesity has great side effects on health. Obesity is associated with increased mortality, BMI over 30 has a risk of death caused mainly by cardiovascular causes. The purpose of this study: to determine the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…According to the results, obese women with triplet pregnancy have a 3 to 4 times risk of experiencing preeclampsia than women of healthy weight. 18 Other research results demonstrated that the obesity body mass index is associated with increased blood pressure, 19 and there is a significant relationship between maternal weight gain during pregnancy with the birth weight of the baby. 20 Previous research has revealed that triplet pregnancy can be detected at 7-8 weeks of pregnancy through an ultrasound examination.…”
Section: Why In This Case Of Triplet Pregnancy and Severe Preeclampsmentioning
confidence: 99%
“…According to the results, obese women with triplet pregnancy have a 3 to 4 times risk of experiencing preeclampsia than women of healthy weight. 18 Other research results demonstrated that the obesity body mass index is associated with increased blood pressure, 19 and there is a significant relationship between maternal weight gain during pregnancy with the birth weight of the baby. 20 Previous research has revealed that triplet pregnancy can be detected at 7-8 weeks of pregnancy through an ultrasound examination.…”
Section: Why In This Case Of Triplet Pregnancy and Severe Preeclampsmentioning
confidence: 99%